Public Health Field Experience Report - Rockler, Briana (My University, 2015)
My public health field experience was completed with HealthKind, a 501(c)(3) non-profit organization located within the Posner Center for International Development in Denver, Colorado. I dedicated one hundred and eighty hours to HealthKind between May 19 and July 21, 2014. HealthKind is a small non-profit organization focused on health and development. The group works for and alongside South Sudanese nationals living in the U.S. in an effort to bring sustainable, community-based and integrative health initiatives to their home country. Initiatives focus on health education, health-worker education, and delivery of services. Founded in 2008 by Rhonda Parmley (Program Director) and Kuier Atem Deng (Country Liason), HealthKind is staffed with seven part-time workers and managed by an advisory board of eleven global health professionals. Four members on staff were South Sudanese refugees who are now active in the diaspora community in Denver. The organization commonly collaborates with other non-profit organizations and policy groups that have a shared interest in improving global health disparities. The characteristic that sets HealthKind apart from other like organizations is their employ of a CEnR approach in addressing the complex health problems that plague South Sudan. By engaging the South Sudanese diaspora community through a grassroots approach, HealthKind is better equipped to identify problems and create health interventions that are both evidence-based and socioculturally appropriate. Current initiatives include the goal to build a health clinic in Kongor, located in Twic East County of the Jonglei State. Ultimately, the aim is to recruit and train South Sudanese living in the U.S. to act as on-the-ground trainers in their native country to both build the healthcare workforce and staff the HealthKind clinic. The goal of the HealthKind clinic is ultimately to serve as a conduit for health initiatives in the country. While in Denver, I worked directly with the Program Director. Dr. Rhonda Parmley holds a Ph.D. in Education and Human Resource Studies, is an Instructor of Women’s Studies at Front Range Community College, and is a guest lecturer on Global Issues in Women’s Health at the Colorado School of Public Health. She is also a Licensed Professional Counselor. As the Program Director and Co-Founder of HealthKind, Dr. Parmley manages all organizational activities from networking to implementing the organization’s programs on the ground. I felt honored to be selected as a practicum student with HealthKind, as global health and community development are fields of special interest to me. Additionally, I believed that my public health education would benefit greatly. Throughout my field experience, I was involved in all aspects of running a global non-profit organization – an experience that was both educational and enlightening.
Keywords: HealthKind; South Sudan; Childhood Overweight; Public Health (0573)